The Impact of Hatha Yoga on Musculoskeletal Complaints in Housewives - Zalfa Afifah Putri Widiarso; Rina Kurnia; Zahira Alya Putri W; Winarni Winarni (International Journal of Health and Social Behavior, 2024)
Musculoskeletal disorders (MSDs) arise from prolonged minor and major repetitive impacts, causing pain in muscles, bones, and joints. Hatha yoga, as a complementary therapy, has the potential to alleviate joint pain. This study aimed to evaluate the effects of hatha yoga on musculoskeletal complaints among housewives in Sindon Village, Ngemplak, Boyolali. Using a pre-experimental design with a one-group pre-test and post-test method, the study involved 30 purposively selected participants. Data were collected using the Nordic Body Map (NBM) questionnaire. Participants underwent 12 hatha yoga sessions over four weeks. The findings indicated a significant reduction in musculoskeletal complaints after the intervention.